Efficient fractionation of moso bamboo by synergistic hydrothermal-deep eutectic solvents pretreatment. (May 2021) - Wang, Ruizhen; Wang, Kui; Zhou, Minghao; Xu, Junming; Jiang, Jianchun
Graphical abstract: Highlights: Hydrothermal-deep eutectic solvents pretreatment exhibited outstanding performance. More than 86.9% of lignin was obtained with up to 99.49% purity. Almost all of the cellulose was retained in residues with purity as high as 92.7%. Both of the water and DESs could be efficiently retrieved. Abstract: As an attractive renewable carbon resource, lignocellulose could be exploited to produce high-value-added products. Notably, comprehensive utilization of lignocelluloses and lignin first exploitation is still a challenge during bio-refinery process. In this study, an environmentally benign extraction method via hydrothermal-deep eutectic solvents pretreatment was proposed to separate hemicelluloses and high purity of lignin simultaneously from moso bamboo with most of cellulose retaining in the residues. Hemicelluloses were firstly removed by hydrothermal pretreatment, following with lignin extraction by DESs which was prepared from choline chloride and lactic acid, betaine and lactic acid, respectively. Notably, 98.2 wt% of hemicelluloses were degraded and mainly converted into pentose. Meanwhile, 80.1 wt% of delignification was achieved under the optimum condition (CC/LA, 140℃, 6 h), following with up to 99.49% of lignin purity. The mass balance evaluation demonstrated that the combined hydrothermal-deep eutectic solvents pretreatment is a potential method for efficient fractionation of lignocellulose.